Feasibility Study on the Removal of Nitric Oxide (NO) in Gas Phase using Dielectric Barrier Discharge Reactor - Hashim, Siti Aiasah; C.S, Wong; Radzi Abas, Mhd.; Hj. Dahlan, Khairul Zaman (Malaysian Journal of Science, 2017)
An initial study was carried out to observe the effect of dielectric barrier discharge on nitric oxide. A dielectric barrier discharge reactor unit consisting of a high voltage power supply and a coaxial dielectric barrier discharge tube was used. The discharge was observed to occur randomly, producing plasma with high energy particles. Technical air consisting of known concentration of nitric oxide, NO, was passed through the discharge. The NO concentration was measured continuously using an NO_x analyzer. This study shows that the removal rate of NO is highly dependent on the discharge voltage. Other factors influencing the removal rate is the gas flow rate and geometrical arrangement of the tubes.